2015
DOI: 10.7448/ias.18.1.19317
|View full text |Cite
|
Sign up to set email alerts
|

Active and latent tuberculosis among HIV‐positive injecting drug users in Indonesia

Abstract: IntroductionInjecting drug use (IDU) is associated with tuberculosis but few data are available from low-income settings. We examined IDU in relation to active and latent tuberculosis (LTBI) among HIV-positive individuals in Indonesia, which has a high burden of tuberculosis and a rapidly growing HIV epidemic strongly driven by IDU.MethodsActive tuberculosis was measured prospectively among 1900 consecutive antiretroviral treatment (ART)-naïve adult patients entering care in a clinic in West Java. Prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
3
6
2
2
Order By: Relevance
“…In this study, TST and T-SPOT.TB detected latent tuberculosis infection in 19% and 18% of the participants, respectively. A study of latent tuberculosis among drug-users with HIV infection in Indonesia revealed a prevalence of 29% using QuantiFERON Gold In-Tube assay, another type of IGRA 21. This prevalence is higher than that found in our study using T-SPOT.TB.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In this study, TST and T-SPOT.TB detected latent tuberculosis infection in 19% and 18% of the participants, respectively. A study of latent tuberculosis among drug-users with HIV infection in Indonesia revealed a prevalence of 29% using QuantiFERON Gold In-Tube assay, another type of IGRA 21. This prevalence is higher than that found in our study using T-SPOT.TB.…”
Section: Discussioncontrasting
confidence: 81%
“…This prevalence is higher than that found in our study using T-SPOT.TB. The higher prevalence could be attributable to the different type of IGRA that was used, the higher proportion of participants who had household exposure to tuberculosis (10%–30%), and the high proportion of participants who had previously been treated for tuberculosis (approximately 40%) 21…”
Section: Discussionmentioning
confidence: 99%
“…In Quebec city, Canada, primary care physicians initiated a substantial number of LTB i treatments, but less than half of patients completed treatment regardless of the physician specialty. Primary care physicians should be supported to enhance treatment completion 25 . PLWHA present a much higher risk of developing TB than the general population and deserve more attention when receiving treatment for LTB i 17 .…”
Section: Discussionmentioning
confidence: 99%
“…De fato, observa-se que as duas infecções, TB e HIV/AIDS, apresentam predominância entre o gênero masculino 34,35 , semelhantemente à prevalência da ILTB que tem sido elevada neste gênero 11,12 . Os resultados podem ser justificados devido a, frequentemente, os homens serem associados à menor adoção de ações de promoção e prevenção em saúde e, por sua parte, menor procura por serviços de saúde 36 , vindo a adoecer e até morrer por doenças como a TB e AIDS 34,35 .…”
Section: Cad Saúde Pública 2017; 33(8):e00050916unclassified
“…No que tange aos fatores associados à ILTB em PVHA, alguns estudos apontam o etilismo 11 , o uso de drogas injetáveis 12 , estágio avançado do HIV, ambientes insalubres e gênero feminino 13 . Outra questão emblemática diz respeito à instituição do tratamento entre os casos de ILTB; na literatura há relatos de pacientes que, mesmo com diagnóstico de ILTB, desenvolveram TB ativa, pois não foram indicados à terapia com isoniazida 14 ; outro fator determinante para adoecimento das PVHA é a não instituição precoce e uso regular da terapia antirretroviral (TARV), sendo que esta terapia pode reduzir em até 51% as chances de desenvolver a TB ativa 15 .…”
Section: Introductionunclassified